Viagem à Lua - Ferreira, Lorena Rodrigues (2017)
TRIP TO THE MOON This work was done considering the possibility of including pre-adolescents and adolescents in scientific research involving the simulation of a space travel to the Moon in a space similar to a spacecraft capable of behaving up to 6 crew members. Faced with the essential need to have an informal teaching environment for the areas of physics, chemistry and science, the simulator is comparable to a desert mirage where the various areas of research can be explored synchronically using the various technological and scientific tools to stimulate the curiosity of young people to take an interest in science and from there, to develop a meaningful learning in relation to those who do not use informal environments. The moon trip simulator is the necessary instrument to fill these gaps, adding to the possibility of insertion of young people trained in simulators like this, to be integrated into the short and medium duration space travel crew, undoing all the frontiers of Science, in especially, Astrophysics. The simulator is composed of diverse environments that resemble those found in real spacecraft, equipped with materials necessary for the execution of didactic-pedagogical, physical and other experimental activities included in this study. The formation of a multiprofessional team is crucial for the planning and execution of the Project as well as obtaining the positive results.